1989
DOI: 10.1515/botm.1989.32.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activity of Extracts from the Rhizomes of the Mediterranean Seagrass Posidonia oceanica (L.) Delile

Abstract: Aqueous and lipid extracts from the rhizomes of the Mediterranean seagrass, Posidonia oceanica have been studied for their antimicrobial activity. The extracts were active against bacteria (Gram" 1 " and Gram"), dermatophytes and the yeast, Malassezia furfur, whereas other yeasts, moulds and the phytofungi tested all proved resistant.This procedure yielded a biphasic system of chloroform-methanol water (2:2:1,8 V/V) following the method described by Bligh and Dyer (1959). The lipid and the aqueous phases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…This extensive and high activity found in our samples had never been observed in other Mediterranean surveys (Caccamese and Azzolina 1979, Caccamese et al 1980, Pesando and Caram 1984, Bernard and Pesando 1989. The most dominant plants in Mediterranean phytobentic communities such as the seagrasses, Cystoseira spp., Halopteris spp., Codium spp., Halimeda tuna, Corailina elongata and Mesophyllum lichenoides strongly inhibited the growth of fungi.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…This extensive and high activity found in our samples had never been observed in other Mediterranean surveys (Caccamese and Azzolina 1979, Caccamese et al 1980, Pesando and Caram 1984, Bernard and Pesando 1989. The most dominant plants in Mediterranean phytobentic communities such as the seagrasses, Cystoseira spp., Halopteris spp., Codium spp., Halimeda tuna, Corailina elongata and Mesophyllum lichenoides strongly inhibited the growth of fungi.…”
Section: Resultssupporting
confidence: 67%
“…Munro et al 1991). Antibacterial, antifungal and antiviral activities have also been investigated in some Mediterranean algae (Berti et al 1963, Khaleafa et al 1975, Porzi and Minelli 1975, Caccamese and Azzolina 1979, Barbagallo et al 1979a, b, Serarols et al 1982, Pesando and Caram 1984, Caccamese et al 1980 and the seagrass Posidonia oceanica Clement 1983, Bernard andPesando 1989). The goal of this study was to increase the knowledge of the chemically-mediated bioactivity in the marine Mediterranean flora by examining its most representative macrophytes, including species not previously tested, and performing antimitotic and cytotoxic tests.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study consisted with some preceding studies of seagrass antibacterial activity (Rengasamy et al, 2008). Similarly extracts from Cymodocea rotundata Ehrenberg and Hemprich ex Ascherson (Cymodoceaceae) was effective against Bacillus species (Bernard & Pesando, 1989). It was reported that ethanol and methanol extracts of seagrasses showed better zones of inhibition against bacterial pathogens (Thirumaran et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous and lipid extracts from the rhizomes of P. oceanica were found to be active aganist selected bacteria (Gramþ and GramÀ), dermatophytes, and the yeasts (Bernard & Pesando, 1988) besides the antileishmanial activity (Orhan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%